2017 Fifteenth IAPR International Conference on Machine Vision Applications (MVA) 2017
DOI: 10.23919/mva.2017.7986849
|View full text |Cite
|
Sign up to set email alerts
|

Can fully convolutional networks perform well for general image restoration problems?

Abstract: We present a fully convolutional network(FCN) based approach for color image restoration. FCNs have recently shown remarkable performance for high-level vision problem like semantic segmentation. In this paper, we investigate if FCN models can show promising performance for low-level problems like image restoration as well. We propose a fully convolutional model, that learns a direct end-to-end mapping between the corrupted images as input and the desired clean images as output. Our proposed method takes inspi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
2

Relationship

3
7

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 15 publications
1
19
0
Order By: Relevance
“…Finally, we study the concrete example of denoising an image corrupted by Beta noise. Many algorithms have been developed so far for the removal of additive white Gaussian noise [ 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 ] which, to some extent, can also be applied for denoising of an image corrupted by Beta noise. However, we here show that the proposed Beta-MCA model is better suited for this task as it assumes a Beta observation noise.…”
Section: Methodsmentioning
confidence: 99%
“…Finally, we study the concrete example of denoising an image corrupted by Beta noise. Many algorithms have been developed so far for the removal of additive white Gaussian noise [ 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 ] which, to some extent, can also be applied for denoising of an image corrupted by Beta noise. However, we here show that the proposed Beta-MCA model is better suited for this task as it assumes a Beta observation noise.…”
Section: Methodsmentioning
confidence: 99%
“…Köhler et al 22 showed a mask specific deep neural network-based blind inpainting technique for filling in small missing regions in an image. Chaudhury et al 23 attempted to solve this problem by proposing a lightweight fully convolutional network and demonstrated that their method can achieve comparable performance as the sparse coding-based K-singular value decomposition 24 technique. However, these inpainting approaches were limited to very small sized masks.…”
Section: Deep Learning-based Inpaintingmentioning
confidence: 99%
“…Kohler et al [54] showed a mask specific deep neural network-based blind inpainting technique for filling in small missing regions in an image. Chaudhury et al [58] attempted to solve the blind image inpainting task using a lightweight fully convolutional network (FCN) demonstrating a comparable performance with the sparse coding based k singular value decomposition (K-SVD) [59] technique. However, initially, CNN-based image inpainting approaches were limited to very small sized masks.…”
Section: Cnn-based Inpaintingmentioning
confidence: 99%